Pengaruh Content Marketing, User-Generated Content, dan Brand Awareness terhadap Keputusan Pembelian pada Kosmetik Lokal - Puji Widia Andari; Lies Handrijaningsih (Journal of Economic and Business Advancement, 2026)
The research aims to analyze the influence of content marketing, user-generated content, and brand awareness on consumer purchasing decisions for kosmetik products, as well as to identify the most dominant variable. Using a quantitative approach, the research involved 130 respondents who had purchased kosmetik products at least once, selected through purposive sampling. Primary data were collected through online questionnaires and analyzed using SPSS with validity tests, reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination. The findings indicate that content marketing, user-generated content, and brand awareness simultaneously affect purchasing decisions. Partially, all three variables also have a positive and significant effect, with brand awareness emerging as the most dominant factor influencing consumers’ purchasing decisions..